INTERNALIZING THE VALUE OF UNITY IN THE THIRD PRINCIPLE OF PANCASILA THROUGH LEGO-LEGO DANCE IN ALOR REGENCY - Maria Antoneta Karbeka; Intan Nurasiah; Suyato; Ranita Eka Desti Rahmawati; Ariani Songli (SOSIOEDUKASI, 2025)
This study aims to analyse the internalisation of the value of unity in the third principle of Pancasila through Lego-Lego dance and its relevance in the era of globalisation. The focus of this study is to discuss the form of internalisation of the value of unity in the third principle of Pancasila through Lego-Lego dance and the relevance of strengthening the value of unity in Lego-Lego dance in the era of globalisation. The method used in this study is a phenomenological approach. This study uses two sources of data, namely primary and secondary data. The primary data consists of in-depth interviews with traditional leaders and civic education teachers. The secondary data consists of documents, scientific articles, and relevant previous studies. The results of this study indicate that the Lego-Lego dance serves as a medium for internalising the value of unity through the formation of a circle and holding hands, which symbolises togetherness, music and lyrics that symbolise emotional bonds, collective participation that fosters inclusiveness, and rituals that reinforce the meaning of unity in social life. In the era of globalisation, Lego-Lego as a medium for internalising the value of Unity plays an important role in strengthening national identity, instilling values of tolerance in a multicultural society, becoming a glue for social cohesion, and also functioning as a medium for learning Citizenship Education.